Pengaruh Faktor-Faktor Penentu Perataan Laba terhadap Return Saham pada Perusahaan Perata Laba di Industri Manufaktur - Panggabean, Rosinta Ria; Novita, Novita (Binus Business Review, 2012)
Income smoothing is the way that used by management to reduce fluctuation in reported earnings to fit the desired target. Income smoothing action is considered as a common action done by management to achieve certain purposes. The purpose of this research is to analyze the influence of determinant factors of income smoothing (net earnings, total asset, total sales, leverage, and operating profit margin) toward stock return. Thesample used in this research is 48 manufacturing companies listed in Indonesian Stock Exchange selected by purposive sampling method. Eckel Index is used in this research as the assumption of income smoothing. The data analysis methods that been used are classical assumption test that included test of normality with One Sample Kolmogorov-Smirnov, multicollinearity test, autocorrelation test, and heteroskedastisity test withscatterplot. Moreover, data are also analyzed using regression test with f test and t test.Based on the result of this research, it is shown that only the net earnings which have a significant influence on stock returns. While, total assets, total sales, leverage, and operating profit margin have no influence on stock returns. Result of this research which conducted by f test (simultaneous test) showed that all independent variables (net earnings, total assets, total sales, leverage, and operating profit margin), together have a significant influence on stock returns.